2019
DOI: 10.1002/smll.201804713
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of the Induced‐Fit Effect in Molecular Self‐Assembly

Abstract: Molecular recognition is a crucial driving force for molecular self‐assembly. In many cases molecules arrange in the lowest energy configuration following a lock‐and‐key principle. When molecular flexibility comes into play, the induced‐fit effect may govern the self‐assembly. Here, the self‐assembly of dicyanovinyl‐hexathiophene (DCV6T) molecules, a prototype specie for highly efficient organic solar cells, on Au(111) by using low‐temperature scanning tunneling microscopy and atomic force microscopy is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…More importantly, our results demonstrate how key features in the HR-AFM image directly arise from the chemical properties and environment (large model) of the molecule, providing thus a qualitative access to those features via the HR-AFM images. Our new results are complementary to recent studies demonstrating the impact of the wider environment of the molecule on the image [36,37,38]. In particular, we show how the electron withdrawing character of the carboxylic groups plays a crucial role in the HR-AFM contrast.…”
Section: Introductionsupporting
confidence: 83%
“…More importantly, our results demonstrate how key features in the HR-AFM image directly arise from the chemical properties and environment (large model) of the molecule, providing thus a qualitative access to those features via the HR-AFM images. Our new results are complementary to recent studies demonstrating the impact of the wider environment of the molecule on the image [36,37,38]. In particular, we show how the electron withdrawing character of the carboxylic groups plays a crucial role in the HR-AFM contrast.…”
Section: Introductionsupporting
confidence: 83%
“…As a crucial activation receptor, NKG2D can specifically bind to DAP10 via the induced fit theory and further induce phosphorylation [54]. The meaning of induced fit theory is shown that when two molecules recognize and combine with each other, molecular flexibility plays a key role in the induced-fit effect to complete self-assembly [55]. DAP10, a kind of DNAX-associated protein 10, is related to the YxxM motif.…”
Section: Interaction Between Nkg2d and Ligandsmentioning
confidence: 99%
“…The calculations were performed using the GAUSSIAN 09 program package with the B3LYP exchange−correlation functional and the 6-31G basis set. 26 As shown before, 37,46 the Au(111) substrate plays a negligible role in the bonding geometry and electronic states of the dicyanovinylenesubstituted oligothiophenes and their assemblies. The intact herringbone reconstruction is an indication of the weak influence of the Au(111) on the chains (see Figures S1 and S2 in the Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 85%